One-step synthesis of Ag–reduced graphene oxide nanocomposites and their surface-enhanced Raman scattering activity. Issue 4 (7th October 2014) - Lin, S.; Zhao, X. S.; Li, Y. F.; Liang, C.; Huang, K.; Sheng, Y.; Wang, H.; Ye, C. X.; Xu, X.; Zhou, Y. F.; Fan, D. Y.; Shang, Y. F.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Ag–reduced graphene oxide (Ag/rGO) nanoparticle composites were synthesized through a facile one-step hydrothermal reaction using GO and silver carbonate (Ag2CO3) as raw materials. The homogeneous silver nanospheres with an average size of 50 nm well dispersed on the surface of rGO were obtained without other additives. During the formation process, GO both promotes the dispersion of Ag2CO3 in aqueous solution and acts as the substrate of silver cations, and the hydrolysis of Ag2CO3 provides silver cations and alkaline condition. Moreover, GO further serves as reducing agent to generate elemental silver in the alkaline condition. The as-prepared materials exhibit excellent surface-enhanced Raman scattering activities when used to detect the Raman signals of R6G absorbed on the Ag/rGO substrate.